Synthesis of Novel 2-Amino-substituted 6-Methyl-pyrimidin-4-ol Derivatives and Their Biological Evaluation - Yengoyan, Aleksandr P.; Pivazyan, Vergush A.; Ghazaryan, Emma A.; Azaryan, Zhermen A. (Letters in Organic Chemistry, 2019)
A series of novel derivatives based on 2-amino-substituted 4-methylpyrimidin-4-ols were synthesized by simple, accessible and efficient methods. 4-N-triazolyl derivatives were obtained from the corresponding 4-chloro derivatives, and O-substituted products, including compounds with a combination of the pyrimidine and oxadiazole rings in the molecule, were synthesized from the sodium salts of 2-amino-substituted pyrimidin-4-ols. The synthesized compounds showed a pronounced stimulating action on plants growth. Their growth stimulant activities were in the range of 46-93% compared to heteroauxin.
Keywords: heteroauxin